Students' Perceptions and Experiences of Online Cooperative Problem-Based Learning: Developing 21st Century Skills - Towip Towip; Indah Widiastuti; Cucuk Wawan Budiyanto (International Journal of Pedagogy and Teacher Education, 2022)
Cooperative problem-based learning (CPBL) has been introduced in engineering education as an effective technique for developing students' professional skills. Moreover, the method is essential for engaging students in learning and developing 21st century skills. However, students are usually "shocked" by such inquiry learning because they face sudden changes in the learning environment. In addition, its implementation in online learning is another challenge. Therefore, this study aims to identify students' perceptions of online CPBL performance in vocational pre-teacher education institutions. A self-reporting questionnaire was designed focusing on 21st century skills and distributed to 71 students after the end of the semester. Quantitatively, the instrument of the survey data was analysed using SPSS software. Quantitative data were analysed using descriptive statistics. The results show that online CPBL improved students’ collaboration, communication, and problem-solving skills. In general, they agreed that online CPBL improved the development of 21st century skills.However, the students faced some difficulties during the online discussion session due to internet connection problems and team member involvement. Details of the items are also discussed.